A survey of cyclic and linear siloxanes in indoor dust and their implications for human exposures in twelve countries. (May 2015) - Tran, Tri Manh; Abualnaja, Khalid O.; Asimakopoulos, Alexandros G.; Covaci, Adrian; Gevao, Bondi; Johnson-Restrepo, Boris; Kumosani, Taha A.; Malarvannan, Govindan; Minh, Tu Binh; Moon, Hyo-Bang; Nakata, Haruhiko; Sinha, Ravindra K.; et al.
Abstract: Siloxanes are used widely in a variety of consumer products, including cosmetics, personal care products, medical and electrical devices, cookware, and building materials. Nevertheless, little is known on the occurrence of siloxanes in indoor dust. In this survey, five cyclic (D3–D7) and 11 linear (L4–L14) siloxanes were determined in 310 indoor dust samples collected from 12 countries. Dust samples collected from Greece contained the highest concentrations of total cyclic siloxanes (TCSi), ranging from 118 to 25, 100 ng/g (median: 1380), and total linear siloxanes (TLSi), ranging from 129 to 4990 ng/g (median: 772). The median total siloxane (TSi) concentrations in dust samples from 12 countries were in the following decreasing order: Greece (2970 ng/g), Kuwait (2400), South Korea (1810), Japan (1500), the USA (1220), China (1070), Romania (538), Colombia (230), Vietnam (206), Saudi Arabia (132), India (116), and Pakistan (68.3). TLSi concentrations as high as 42, 800 ng/g (Kuwait) and TCSi concentrations as high as 25, 000 ng/g (Greece) were found in indoor dust samples. Among the 16 siloxanes determined, decamethylcyclopentasiloxane (D5) was found at the highest concentration in dust samples from all countries, except for Japan and South Korea, with a predominance of L11; Kuwait, with L10; and Pakistan and Romania, with L12. The composition profiles of 16 siloxanes in dust samples varied by country. TCSi accounted for a major proportion of TSi concentrations in dust collected from Colombia (90%), India (80%) and Saudi Arabia (70%), whereas TLSi predominated in samples collected from Japan (89%), Kuwait (85%), and South Korea (78%). Based on the measured median TSi concentrations in indoor dust, we estimated human exposure doses through indoor dust ingestion for various age groups. The exposure doses ranged from 0.27 to 11.9 ng/kg-bw/d for toddlers and 0.06 to 2.48 ng/kg-bw/d for adults. Graphical abstract: Highlights: 5 cyclic and 11 linear siloxanes were determined in 310 indoor dust from 12 countries. Linear siloxane concentrations as high as 42, 800 ng/g and cyclic siloxanes as high as 25, 000 ng/g were found. Decamethylcyclopentasiloxane (D5) was found at the highest concentration in dust from most countries. The exposure doses of siloxanes through dust were below 10 ng/kg-bw/d.